2019
DOI: 10.21608/ejmm.2019.282671
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Associated Infections Caused by Gram-negative Bacilli in Adult Intensive Care Units: Identification of AmpC Beta-Lactamases Mediated Antimicrobial Resistance

Abstract: Healthcare associated infections (HAIs) caused by AmpC β-lactamases producers are clinically significant as they can mediate resistance to cephalosporins, penicillins, monobactams and cephamycins. Objectives: To find out the prevalence of AmpC producers among Gram-negative bacilli recovered from HAIs in adult intensive care units (ICUs) and to identify the risk factors associated with AmpC β-lactamases production. In addition, we compared the antimicrobial resistance patterns in AmpC positive and negative isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…In this study, a higher percentage of AmpC production was observed among A. baumannii (30%), followed by K. pneumoniae (12.5%) than among E. coli isolates (2%). A similar finding was observed by Sultan et al who reported that 44.4% of A. baumannii isolates were AmpC-producers, which was greater than the AmpC production rates of E. coli (35.5%) and K. pneumoniae (30.4%) [ 30 ]. Yilmaz et al found that 10% of K. pneumoniae isolates were AmpC-producers and 0.9% in E. coli [ 31 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, a higher percentage of AmpC production was observed among A. baumannii (30%), followed by K. pneumoniae (12.5%) than among E. coli isolates (2%). A similar finding was observed by Sultan et al who reported that 44.4% of A. baumannii isolates were AmpC-producers, which was greater than the AmpC production rates of E. coli (35.5%) and K. pneumoniae (30.4%) [ 30 ]. Yilmaz et al found that 10% of K. pneumoniae isolates were AmpC-producers and 0.9% in E. coli [ 31 ].…”
Section: Discussionsupporting
confidence: 83%
“…A lower rate was recorded by another study which showed AmpC production in 2.6% of studied Enterobacterales isolates [ 27 ], whereas higher percentage rates of 28.3% and 19.5% were reported [ 28 , 29 ]. Sultan et al reported that 49% of GNB isolates were AmpC-producers [ 30 ]. The observed differences in prevalence rates could be attributed to various factors such as variations in the geographic regions, sample sizes, types of specimens analyzed, the specific species of bacteria isolated, study population, and the extent of antibiotic usage in different settings [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study recorded a 20.9% resistance rate to imipenem [44]. Sultan et al observed lower resistance rates to imipenem and meropenem (13.7, and 8.2%, respectively) among AmpCproducers isolates [35]. The least effective carbapenem evaluated in our investigation was ertapenem (68% sensitivity).…”
Section: Discussionmentioning
confidence: 44%
“…Most of our isolates were resistant to both combinations (72.35% and 78.73%, respectively). Sultan et al reported a 97.3% resistance rate to piperacillin-tazobactam among AmpCproducer isolates [35].…”
Section: Discussionmentioning
confidence: 99%